Normal Platelet Aggregating Properties of Ehlers-Danlos Syndrome “Collagen” - Deliyannis, Angelo A.; Kontopoulou-Griva, Irene; Tsevrenis, Hippocrates V. (Thrombosis and Haemostasis, 1974)
Normal platelet aggregating activity of collagen taken from a patient with Ehlers-Danlos syndrome is reported.